2013 35th International Conference on Software Engineering (ICSE) 2013
DOI: 10.1109/icse.2013.6606639
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining ground-truth software architectures

Abstract: Undocumented evolution of a software system and its underlying architecture drives the need for the architecture's recovery from the system's implementation-level artifacts. While a number of recovery techniques have been proposed, they suffer from known inaccuracies. Furthermore, these techniques are difficult to evaluate due to a lack of "ground-truth" architectures that are known to be accurate. To address this problem, we argue for establishing a suite of ground-truth architectures, using a recovery framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 24 publications
2
55
0
Order By: Relevance
“…In some cases, researchers have used directory or package structure as a widely available architectural proxy. However, our recent study [19] has shown that in most real systems, architects do not consider the directory or package structure to be an accurate reflection of a system's architecture. Finally, the above studies give little guidance as to the conditions under which a recovery technique excels or falters.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, researchers have used directory or package structure as a widely available architectural proxy. However, our recent study [19] has shown that in most real systems, architects do not consider the directory or package structure to be an accurate reflection of a system's architecture. Finally, the above studies give little guidance as to the conditions under which a recovery technique excels or falters.…”
Section: Related Workmentioning
confidence: 99%
“…The systems' eight architectures comprise our ground truth. Four of the architectures-those of ArchStudio, Bash, Hadoop, and OODT-were verified as correct by one or more architects of the corresponding systems [19]; the remaining four architectures-two each of Linux and Mozilla-are a result of a meticulous recovery process conducted by other researchers and were used in previous evaluations of recovery techniques [6]. Our assessment is performed at the system-wide level and at the level of individual system components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garcia et al [12] proposed a systematic process for recovering the module view of software manually and published the module views of Apache Hadoop, Apache OODT, and ArchStudio. We shall use them as ground-truth results in our experiments.…”
Section: Experiments and Evaluationmentioning
confidence: 99%
“…Nowadays various clustering methods and software dependencies for module view recovery are studied in the field of software reengineering. Due to its usefulness, the research on this topic has been actively pursued [12].…”
Section: Introductionmentioning
confidence: 99%